2007
DOI: 10.1111/j.1365-2893.2007.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased liver mast cell recruitment in patients with chronic C virus‐related hepatitis and histologically documented steatosis

Abstract: Hepatitis C virus (HCV) is still one of the major causes of chronic viral infection worldwide, and hepatic steatosis is a frequent pathological finding in patients with chronic HCV-related diseases. It is unclear whether the steatosis is associated with host factors or the virus itself, although a consistent relationship has been found between steatosis and a necro-inflammatory reaction with the increased secretion of immuno-regulators. A primary sources of inflammatory mediators are mast cells (MCs) bone marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 47 publications
2
15
1
1
Order By: Relevance
“…There was no difference in DMCs between periodontitis and control groups. This is in contrast to a previous study that observed an increase in DMCs in hepatic steatosis 13 . Induced periodontal disease in the current model was also not associated with any alterations in body weights and liver function.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…There was no difference in DMCs between periodontitis and control groups. This is in contrast to a previous study that observed an increase in DMCs in hepatic steatosis 13 . Induced periodontal disease in the current model was also not associated with any alterations in body weights and liver function.…”
Section: Discussioncontrasting
confidence: 99%
“…Hepatic biology has shown the importance of mast cells that are increased in chronic C virus-related hepatitis. 13 In addition, pericytes associated with portal vessels may be niches of cells with a high potential for cell differentiation, as has been demonstrated recently. 14 Moreover, regarding liver disease, in previous years, studies 8,9 have demonstrated an association with periodontitis.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The complement system, as an innate immune mechanism of host defence, plays a role in fibrogenesis via the complement factor 5 (C5) (Hillebrandt et al 2005), whose depletion in mice leads to impaired liver regeneration (Mastellos et al 2001). Innate lymphoid cells (nuocytes), neutrophils, and mast cells are additional cell types that might play a role in fibrogenesis (Franceschini et al 2007; Harty et al 2010; Liang et al 2013), even though the results are not always conclusive (Saito et al 2003; Sugihara et al 1999; Xu et al 2004). Importantly, since the majority of findings discussed here comes from rodent models, additional research is needed to attribute these functions to human counterparts.…”
Section: Additional Pro-fibrogenic Actorsmentioning
confidence: 99%
“…Mast cells are present in normal livers, and their numbers are increased in fatty liver disease (13,14,26). In agreement with these finding, ApoE Ϫ/Ϫ /Kit W-sh/W-sh presented with significantly reduced hepatic steatosis during the first 3 mo of the high-fat regimen.…”
Section: /Kitmentioning
confidence: 99%